You need to remember the formula of the difference of two perfect cubes:

`a^3-b^3 = (a-b)(a^2+ab+b^2)`

Comparing the difference of two cubes to the given equation yields:

`x^3-1 = (x-1)(x^2 + x + 1)`

You need to solve for x the product `(x-1)(x^2 + x + 1)` = 0.

x...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to remember the formula of the difference of two perfect cubes:

`a^3-b^3 = (a-b)(a^2+ab+b^2)`

Comparing the difference of two cubes to the given equation yields:

`x^3-1 = (x-1)(x^2 + x + 1)`

You need to solve for x the product `(x-1)(x^2 + x + 1)` = 0.

x - 1 = 0 => x = 1

Notice that `x^2 + x + 1` > 0 `AA` x `in` R

**The real solution to the given equation is x = 1.**